The Study of Changes in the Physicochemical Properties of the Tigris River from an Environmental Perspective in the Cities of Baiji and Tikrit over a Three Months Period - Al-Quraghuli, Abdullah Zaidan Khalaf; Ali, Jassim Mohammed (American Journal of Biodiversity, 2025)
The current study was conducted to assess the water quality of the Tigris River by measuring certain of its physicochemical parameters. In Salah al-Din Governorate, covering the areas of Tikrit, Al-Hajjaj, and Baiji. Samples were collected over three months, from February 2025 to April 2025, at varying times, at a rate of 180 mL per area per month. The study included measurements of air and water temperatures, turbidity, electrical conductivity, pH, salinity, dissolved solids, dissolved oxygen, total hardness, calcium and magnesium hardness in the river water. The study results showed that the values of air and water temperatures have ranged between (18.3-33.7) ᵒC, (11-18.9) °C in the Tigris River, respectively. Turbidity showed a difference in percentages according to the region, as it recorded its highest degrees in the Baiji region, ranging between NUT (7.976.38). In contrast, Tikrit showed the lowest percentage, which ranged between NUT (1.220.38). Electrical conductivity in study sites recorded values ranged between (2711-9655) µs̷ cm. pH values ranged between (6.6-8.7), and variations were observed in all study areas over the three months. Salinity showed convergence in the results over the three months, and its value ranged between (0.70.4) us/cm. Total dissolved solids showed values that changed throughout the months of study, with the highest value (5800 mg/L) observed at S3. Dissolved oxygen values ranged between 5 and 6 mg/L in the Tigris River. Total hardness, calcium, and magnesium were (700-2000), (580-1090) and (14.16-315.74) mg CaCO3/L, respectively. Statistically significant differences have emerged in all physical and chemical characteristics between months at a probability level (P ≤ 0.05), while there were no differences between stations, except for calcium hardness.